Kitchen confidential? Norms for the use of transferred knowledge in gourmet cuisine - Di Stefano, Giada; King, Andrew A.; Verona, Gianmario (Strategic Management Journal, 2014)
When will knowledge holders share their knowledge with peers? Several studies suggest that norms of knowledge disclosure encourage knowledge transfer. More recently, scholars have hypothesized that norms of knowledge use may indirectly promote it. In this article, we synthesize a theoretical framework of the effect of norms of knowledge use and test its predictions by means of a field experiment involving more than 500 Italian chefs. For the literature on knowledge transfer, we confirm the importance of norms, but we also show that they are not complete substitutes for other means of protecting private knowledge. For the literature on social norms, we provide evidence of how actors assess others' propensity to conform and how this influences the intention to participate in the norm‐regulated exchange . Copyright © 2013 John Wiley & Sons, Ltd.